LINC00511 promotes gastric cancer progression by regulating SOX4 and epigenetically repressing PTEN to activate PI3K/AKT pathway. Issue 19 (24th August 2021) - Wang, Qianwei; Mao, Xiang; Luo, Fen; Wang, Jun
Abstract: Gastric cancer (GC) serves as a common malignancy. Long non‐coding RNAs (lncRNAs) have been proven to regulate many cancers, including GC. Long intergenic non‐protein‐coding RNA 511 (LINC00511) has been poorly studied in GC, but its detailed regulatory mechanism has not been identified. Here, LINC00511 was detected to be highly expressed in GC cells. Functional assays were conducted and uncovered that LINC00511 boosted cell proliferation, migration, stemness and EMT process while inhibiting the apoptosis of GC cells. From a series of mechanism experiments, it was found that at the transcriptional level, LINC00511 recruited EZH2 (enhancer of zeste 2 polycomb repressive complex 2 subunit) to the promoter of PTEN (phosphatase and tensin homolog) and facilitated methylation of PTEN promoter. LINC00511 epigenetically repressed PTEN to activate the PI3K/AKT pathway. Moreover, SRY‐box transcription factor 4 (SOX4) activated the transcription of LINC00511. At the post‐transcriptional level, LINC00511 sponged miR‐195‐5p to elevate SOX4 expression in GC cells. On the whole, the present study disclosed that SOX4‐induced LINC00511 activated SOX4 via competing endogenous RNA (ceRNA) pattern and epigenetically repressed PTEN to activate PI3K/AKT pathway by recruiting EZH2, thus facilitating GC cell proliferation, migration and stemness while inhibiting GC cell apoptosis.